Rehabilitation of patients with high-energy multiple injuries of long bones of their lower extremities - Krivenko, Sergey; Grebeniuk, Anatoliy; Volkova, Alesya; Ivashutin, Dmitriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Restorative treatment of patients with high-energy multiple injuries of long bones of their lower extremities takes one of the first places among measures for resuming the social and occupational fitness of the victims. Patients with a delayed restoration of movements in joints received, side by side with physiofunctional treatment, the authors’ device for active unaided exercising of movements in the knee joint (Patent of Ukraine No. 21435A). The combined tactics of treatment with use of external osteosynthesis for closed oblique, transverse, short oblique and comminuted femoral fractures, and transosseous osteosynthesis for fractures of the shin irrespective of their character, as well as an individual complex of remedial gymnastics, physio- and mechanotherapy made it possible to achieve good anatomofunctional results in 86.6 % of cases.